2022
DOI: 10.1590/1518-8345.6034.3699
|View full text |Cite
|
Sign up to set email alerts
|

Creation and validation of a high-fidelity simulation scenario for suicide postvention

Abstract: Objective to create and validate a high-fidelity simulation scenario about the initial support to suicide bereaved people. Method a methodological research study to create and validate a simulation scenario about postvention. Its creation was based on scientific recommendations, the validation process was carried out by experts, based on an instrument developed by the authors; the data were statistically analyzed using the Content Validity Index and Gwet concordance coefficient. Results the scenario was crea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
1
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 41 publications
1
1
0
4
Order By: Relevance
“…This study also aligns with a trend observed in the literature, emphasizing the use of established theoretical frameworks (13,16) in planning clinical simulations and structuring simulated scenarios in various healthcare areas (9)(10)14,22) . The use of such frameworks creates conditions for the simulation-based learning experience to achieve its objectives and increase participant satisfaction and self-confidence in the pedagogical experience (10,(24)(25) .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This study also aligns with a trend observed in the literature, emphasizing the use of established theoretical frameworks (13,16) in planning clinical simulations and structuring simulated scenarios in various healthcare areas (9)(10)14,22) . The use of such frameworks creates conditions for the simulation-based learning experience to achieve its objectives and increase participant satisfaction and self-confidence in the pedagogical experience (10,(24)(25) .…”
Section: Discussionsupporting
confidence: 88%
“…This is the first Brazilian study to construct and validate a clinical scenario for CHWs, presenting the development and validation of a clinical scenario aimed at teaching CHWs about actively searching for leprosy cases. Thus, it contributes to the scientific advancement in the field of health and nursing, as the literature points to the incipience of simulation scenarios that contextualize community work (20) and the need to expand the applicability of this resource to improve the quality of training and professional qualification for work in PHC services (21)(22) . Especially regarding leprosy, research conducted in Brazil highlights the need for training activities for CHWs to carry out leprosy control actions (LCAs) in the territory covered by PHC services (3,(5)(6)23) .…”
Section: Discussionmentioning
confidence: 99%
“…Este é o primeiro estudo brasileiro a realizar a construção e a validação de cenário clínico para ACS e apresentar a elaboração e a validação de cenário clínico voltado ao ensino para ACS de ações de busca ativa da hanseníase. Desse modo, vem contribuir com o avanço científico da área da saúde e da enfermagem, uma vez que a literatura aponta a incipiência de cenários de simulação contextualizando a atuação comunitária (20) e a necessidade de expansão da aplicabilidade do uso desse recurso com vistas à melhoria da qualidade da formação e da qualificação profissional para a atuação em serviços de APS (21)(22) . Especialmente no tocante à hanseníase, pesquisas realizadas no Brasil apontam a necessidade de atividades de capacitação para os ACS realizarem as ACHs no território de abrangência dos serviços de APS (3,(5)(6)23) ; nesse contexto, a presença de ACS capacitado está associada a maiores escores dos atributos essenciais e derivados da APS na realização das ACHs (5) .…”
Section: Discussionunclassified
“…Este estudo também vem integrar um movimento, já observado na literatura, de valorização do uso de referenciais teóricos consagrados (13,16) no planejamento de simulações clínicas e na estruturação de cenários simulados em diferentes áreas da saúde (9)(10)14,22) . A utilização de tais referenciais cria condições para que a experiência de aprendizagem baseada na simulação resulte no alcance dos objetivos propostos e no incremento da satisfação e da autoconfiança dos participantes com a vivência pedagógica (10,(24)(25) .…”
Section: Discussionunclassified
“…Sendo o encerramento abrupto de um elo. Esse processo pode apresentar sofrimento psíquico e complicado, quando a causa da perda é por suicídio, os sobreviventes podem apresentar particularidades no sofrimento, podendo vivenciar emoções, comportamentos, mudanças físicas e psicológicas que diferenciam das outras formas de luto (Pedrollo et al, 2022). Dantas et al (2022), salientam que essas particularidades podem estar correlacionadas por ser uma morte violenta e estigmatizada.…”
Section: Issn (Eletrônico) 2446-922xunclassified